1999
DOI: 10.1117/12.351380
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Army Soldier and Biological Chemical Command counterproliferation long-range biological standoff detection system (CP LR-BSDS)

Abstract: Schwartz Electro-Optics, Inc. (SEO) is developing a second-generation LIDAR-based long range aerosol detection and assessment system called the Counter-Proliferation Long Range -Biological Standoff Detection System (CP LR-BSDS) for the U.S. Army Soldier and Biological Chemical Command (SBCCOM). CP LR-BSDS will be a palletized, self-contained system for use on the Army's UH-60A (Blackhawk) helicopter for long range detection and shape classification of long-line source aerosol clouds. This paper presents the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…a complex OPO laser system requiring a high energy pump laser (commonly a 1 .06 jim Nd:YAG laser). 2. the commonly availablel .5 jim detectors are inherently less sensitive, hence special detectors are needed [Condatore, et a!, 1999], adding to the cost and complexity. On the other hand, since the laser energy required for the PDL is small, a small DPSS Nd:YAG (or Nd:YLF) laser with outputs at the fundamental (1 .06 or 1 .047 jim) and second harmonic (532 or 523 nm) can be used and the laser beams at both wavelengths are easily made eye-safe by expanding the transmitted laser beam to the full aperture of the transmitter/receiver telescope.…”
Section: Comparison Of the Portable Digital Lidar With The Analog Detmentioning
confidence: 99%
See 1 more Smart Citation
“…a complex OPO laser system requiring a high energy pump laser (commonly a 1 .06 jim Nd:YAG laser). 2. the commonly availablel .5 jim detectors are inherently less sensitive, hence special detectors are needed [Condatore, et a!, 1999], adding to the cost and complexity. On the other hand, since the laser energy required for the PDL is small, a small DPSS Nd:YAG (or Nd:YLF) laser with outputs at the fundamental (1 .06 or 1 .047 jim) and second harmonic (532 or 523 nm) can be used and the laser beams at both wavelengths are easily made eye-safe by expanding the transmitted laser beam to the full aperture of the transmitter/receiver telescope.…”
Section: Comparison Of the Portable Digital Lidar With The Analog Detmentioning
confidence: 99%
“…Remote stand-offdetection is thus a critical necessity for providing an early warning for maximum survivability of personnel in the battlefield and other sensitive areas. The pulsed elastic backscatter lidar operating in the visible [Lee, et al, 1997], or near JR [Jezek, et al, 1998, Condatore, et al, 1999 wavelengths has demonstrated high sensitivity and long range (up to 50km) capability for detecting aerosol clouds. But, the single wavelength aerosol lidar does not provide discrimination between BW agent aerosols and other natural or interferent aerosol clouds.…”
Section: Introductionmentioning
confidence: 99%
“…Because the signal to be detected is weak (the objective is to detect bioaerosol clouds having concentrations of 1000 ACPLA or less), the two detection channels will have to be operated in photon counting mode. A mathematical model describing the returned spectrally distributed fluorescence for this prototype can easily be derived from the classical inelastic LIDAR equation2' as: dba (k,2,r) = (r) t0R)t0(2) tai(2o,r)tac(,r) Nba(r) R (2) where dE/dba 5 the spectrally distributed number of photons collected by the LIDAR and r is the range. The term A combines n, the number of laser pulses integrated, E0, the number of transmitted photons per pulse, and Ar, the size of the probed atmospheric cell.…”
Section: Lidar Modellingmentioning
confidence: 99%
“…The amplitude of the return signal is proportional to the number of aerosolized particles present in the probed volume, while the time delay of the return signal is related to the distance from the cloud. Elastic backscatter lidar systems, typically operating in the infrared range (1 to 10 μm) can detect aerosol clouds up to a few tens of kilometers away [3]. Inelastic lidar can procure specific information on the light scattering particles following the absorption and emission of a photon at different frequencies either through a virtual energy level, in the case of Raman lidars, or through a real excited state for the resonant lidars.…”
Section: Introductionmentioning
confidence: 99%